Productivity and biometric characteristics of signal grass in a silvopastural system - Bosi, Cristiam; Pezzopane, José Ricardo Macedo; Sentelhas, Paulo Cesar; Santos, Patricia Menezes; Nicodemo, Maria Luiza Franceschi (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the productivity and biometric characteristics of signal grass (Urochloa decumbens) under grazing, in a silvopastural system. A system with native trees of commercial interest, planted in a set of rows with north-south orientation, with 17 m spacing was evaluated. A randomized complete block design with four replicates was carried out in a split-plot arrangement, with forage grass regrowth cycles evaluated in the plots and distances from trees in the subplots. Seven regrowth cycles were evaluated at four distances of the set of tree rows: at 2 and 6 m from trees at east, and at 2 and 6 m from trees at west. Dry matter productivity, leaf area index (LAI), specific leaf area (SLA), and plant height were measured. Forage productivity in the first two cycles and LAI in the second and third cycles reduced with shading levels higher than 39 and 40%, respectively. However, plant height increased with shadings greater than 53%, in the first four cycles, and SLA with shadings greater than 66%, in the first three cycles.